Recursos educativos digitales de la Web que apoyan el aprendizaje de la asignatura de Ciencias Naturales en el octavo año de educación general básica del Colegio Bachillerato Macará año lectivo 2021 - 2022. - Alvarez Peña, Maria Daniela (2023)
Digital Educational Resources are known for fulfilling a learning achievement by providing didactic contributions to both actors of the educational process; thus, they offer new opportunities in the formation of students, serve as support and improve learning about the curricular content. The purpose of this research is to analyze resources that are part of the web, which support the learning of the subject of Natural Sciences in the eighth year of general basic education; The methodology of the study is based on the deductive method, with a quantitative approach, of a descriptive/exploratory nature, the analysis was carried out based on the matrix of Skills with Performance Criteria (DCD) Science Projects and the Prioritized Curriculum, which allowed systematizing the information and defining the topics of the subject in question, by extracting the essential contents to examine the resources available on the web 2. 0 that support the teaching of Natural Sciences. Keywords: Digital Educational resources, teaching-learning, Natural Sciences subject, Web 2.0.